Feminism and freedom: lexicon and social representation in advertisement - Antonio, Denise Bordin da Silva (2024)
The objective of this work is to reflect on the representation, through the lexicon, of the value of female freedom in advertisements for beauty industry brands. It is understood that the use of lexical units representative of feminist discourse in advertising is a commercial appropriation strategy to reach a target audience and, consequently, contributes to a depoliticization of feminist values, which are now presented as products to be consumed. For the analysis, we started from the transcription of audiovisual advertisements produced between 2015 and 2021, selecting excerpts which present lexical units that symbolize women's freedom, such units were determined to be representative of the feminist lexicon based on a Corpus of the Feminist Lexicon, called Lex-Fem (Antonio, 2022). It was found the presence of lexical units that represent the ideal of freedom in statements related to the products advertised and to practices that traditionally do not distance themselves from impositions made to women. In addition, the excerpts analyzed reveal that the discourse constructed in the commercials does not represent the category of women in their heterogeneity, resulting in productions that dialogue more directly with white women and women from privileged socioeconomic classes, going in the opposite direction to what is proposed by feminist discourses, which present a collective and plural struggle, aiming to meet the specific demands of different women.